Improved plant cytosine base editors with high editing activity, purity, and specificity. Issue 10 (7th June 2021) - Ren, Qiurong; Sretenovic, Simon; Liu, Guanqing; Zhong, Zhaohui; Wang, Jiaheng; Huang, Lan; Tang, Xu; Guo, Yachong; Liu, Li; Wu, Yuechao; Zhou, Jie; Zhao, Yuxin; et al.
Summary: Cytosine base editors (CBEs) are great additions to the expanding genome editing toolbox. To improve C‐to‐T base editing in plants, we first compared seven cytidine deaminases in the BE3‐like configuration in rice. We found A3A/Y130F‐CBE_V01 resulted in the highest C‐to‐T base editing efficiency in both rice and Arabidopsis . Furthermore, we demonstrated this A3A/Y130F cytidine deaminase could be used to improve iSpyMacCas9‐mediated C‐to‐T base editing at A‐rich PAMs. To showcase its applications, we first applied A3A/Y130F‐CBE_V01 for multiplexed editing to generate microRNA‐resistant mRNA transcripts as well as pre‐mature stop codons in multiple seed trait genes. In addition, we harnessed A3A/Y130F‐CBE_V01 for efficient artificial evolution of novel ALS and EPSPS alleles which conferred herbicide resistance in rice. To further improve C‐to‐T base editing, multiple CBE_V02, CBE_V03 and CBE_V04 systems were developed and tested in rice protoplasts. The CBE_V04 systems were found to have improved editing activity and purity with focal recruitment of more uracil DNA glycosylase inhibitors (UGIs) by the engineered single guide RNA 2.0 scaffold. Finally, we used whole‐genome sequencing (WGS) to compare six CBE_V01 systems and four CBE_V04 systems for genome‐wide off‐target effects in rice. Different levels of cytidine deaminase‐dependent and sgRNA‐independent off‐target effects were indeed revealed by WGS among edited lines by these CBE systems. We also investigated genome‐wide sgRNA‐dependent off‐target effects by different CBEs in rice. This comprehensive study compared 21 different CBE systems, and benchmarked PmCDA1‐CBE_V04 and A3A/Y130F‐CBE_V04 as next‐generation plant CBEs with high editing efficiency, purity, and specificity.